Feeding the Mediterranean through knowledge - Adinolfi F.; Petruzzella D.; Giannelli M. (Feeding knowledge, 2017)
One of the main outcomes of “Feeding Knowledge” Programme, a strategic initiative of Expo Milano 2015 jointly planed, co-funded and implemented by CIHEAM Bari and Politecnico of Milano – METID, is a policy paper giving some advice on suitable policy options for establishing a sound knowledge system for food security in the Mediterranean, based on the recommendations of the scientific experts gathered in the “Feeding Knowledge Network” and on the main needs of target countries collected by the Local Points of the Programme. The Paper is the result of a long participatory process, made up of several steps, namely: preliminary draft based on the main recommendations outlined in the five “white papers” and on the results of stakeholders interviews in target countries (200 stakeholders reached); open consultation on www.feedingknowledge.net (that reached 2000 members of FK network); discussion with policy makers, institutional actors and stakeholders from more than 15 Euro-Mediterranean countries on the occasion of an ad-hoc event held in January 2015 in Rome, hosted by the Italian Ministry of Foreign Affairs and International Cooperation. The key messages of the policy paper have been presented at Expo Milano 2015 during the Award Ceremony of the Best Sustainable Development Practices, on July 6th, 2015. This article presents the integral text of the policy paper.
Expo Milano 2015